Introduction to electromagnetism : from Coulomb to Maxwell - Sibley, M. J. N. (Martin J. N.) (Boca Raton : CRC Press, 2021)
"This edition aims to expand the on the first edition and take the reader through to the wave equation on coaxial cable and free-space by using Maxwell's equations. The new chapters will include time varying signals and fundamentals of Maxwell's equation"--
OCLC-licensed vendor bibliographic record.
Keywords: Electromagnetism; SCIENCE / Electromagnetism; TECHNOLOGY / Lasers; TECHNOLOGY / Microwaves